1996
DOI: 10.1111/j.1365-2125.1996.tb00173.x
|View full text |Cite
|
Sign up to set email alerts
|

Venlafaxine oxidation in vitro is catalysed by CYP2D6

Abstract: 1 Several selective 5-HT reuptake inhibitors (SSRIs) are inhibitors of the genetically polymorphic drug metabolizing enzyme, CYP2D6. We studied the interaction of venlafaxine, a new SSRI, with CYP2D6 in human liver microsomes. 2 Venlafaxine was a less potent inhibitor of this enzyme activity in vitro than other SSRIs tested. The average apparent K i values determined using CY P2D6-dependent dextromethorphan 0-demethylation were: 33, 52 and 22 PM for rac-venlafaxine, R( +)-venlafaxine and S (-)-venlafaxine, res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
151
1
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 217 publications
(161 citation statements)
references
References 28 publications
7
151
1
2
Order By: Relevance
“…Our data obtained through the use of multiple experimental methods agrees with, but extends previous studies using only human liver microsomes (Otton et al 1996). Several recent studies have used a combination of methods to achieve a better understanding of the NEUROPSYCHOPHARMACOLOGY 1999-VOL.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Our data obtained through the use of multiple experimental methods agrees with, but extends previous studies using only human liver microsomes (Otton et al 1996). Several recent studies have used a combination of methods to achieve a better understanding of the NEUROPSYCHOPHARMACOLOGY 1999-VOL.…”
Section: Discussionsupporting
confidence: 81%
“…ODV has a receptor affinity profile similar to its parent compound VF, while the latter two metabolites have little if any affinity for the above receptor sites (Muth et al 1991). Previous studies have shown that the biotransformation of VF to ODV is mediated by CYP2D6, and NDV via CYP3A3 ր 4, and possibly a second enzyme (Otton et al 1996).…”
Section: The Biotransformation Of Venlafaxine (Vf) Into Its Two Majormentioning
confidence: 99%
See 2 more Smart Citations
“…It is metabolized by CYP 2D6 isoenzyme of cytochrome P450. 4 VEN induced hepatotoxicity is rare but a life threatening adverse effect and reported in 0.4% of patients. 5 The mechanism for liver injury due to VEN is either immunoallergic in nature, metabolic or due to its intermediate…”
Section: Introductionmentioning
confidence: 99%